Illuminating the intent: an exposition of Candrakīrti's "Entering the middle way" - Blo-bzang-grags-pa (The library of Tibetan classics, 2021)
"This work is an authoritative exposition of Candrakīrti's seventh-century classic Entering the Middle Way. Written primarily as a supplement to Nāgārjuna's Fundamental Verses on the Middle Way, Candrakīrti's text integrates the central insight of Nāgārjuna's thought-the rejection of any metaphysical notion of intrinsic, objective being-with the ethical and edifying elements of the Buddha's teachings. He undertakes this by correlating the progressive stages of insight into the emptiness of intrinsic existence with the well-known Mahayana framework of the ten levels of the bodhisattva. Completed the year before the author's death, Tsongkhapa's exposition of Candrakīrti's text is recognized by the Tibetan tradition as the final standpoint of Tsongkhapa on many of the questions of Buddhist Madhyamaka philosophy. Written in lucid exemplary Tibetan, Tsongkhapa's work presents a wonderful marriage of rigorous Madhyamaka philosophical analysis with a detailed and subtle account of the progressively advancing mental states and spiritual maturity realized by sincere Madhyamaka practitioners. The work is still used as the principal textbook in the study of Indian Madhyamaka philosophy in many Tibetan monastic colleges. Tsongkhapa's extensive writings on Madhyamaka philosophy, including the present text, ushered in a new phase of engagement with the philosophy of emptiness in Tibet, giving rise to a great flowering of literary activity on the subject by subsequent Tibetan scholars like Gyaltsab Jé, Khedrup Jé, and the First Dalai Lama, as well as the critiques of Taktsang Lotsāwa, Gorampa, Shākya Chokden, and Karmapa Mikyö Dorjé and the subsequent responses to these by Tsongkhapa's followers, such as Jamyang Galo, Jetsun Chökyi Gyaltsen, and Panchen Losang Chögyen"--